Information Communication Technology in Education: Bringing Innovation in Classroom - Upadhayaya, Parshu Ram (Ganeshman Darpan, 2023)
ICT (Information Communication Technology) has revolutionized education by bringing innovation into the classroom. This paper explores the integration of four key elements: learning through games and gamification, Bring Your Own Device (BYOD) and mobile education, learning with adaptation and artificial intelligence (AI), and online cooperation and connections. The study examines the benefits and implications of these innovative approaches in enhancing teaching and learning experiences. It highlights how games and gamification engage students and promote active learning, while BYOD and mobile education provide flexibility and access to educational resources. Additionally, it discusses the personalized learning opportunities offered by adaptation and AI, as well as the collaborative and global connections fostered through online cooperation. The research underscores the importance of these elements in transforming education and preparing students for the challenges of the digital era.